2012
DOI: 10.1124/mol.112.078956
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone Heat Shock Protein 90 Mobilization and Hydralazine Cytoprotection against Acrolein-Induced Carbonyl Stress

Abstract: Toxic carbonyls such as acrolein participate in many degenerative diseases. Although the nucleophilic vasodilatory drug hydralazine readily traps such species under "test-tube" conditions, whether these reactions adequately explain its efficacy in animal models of carbonyl-mediated disease is uncertain. We have previously shown that hydralazine attacks carbonyl-adducted proteins in an "adduct-trapping" reaction that appears to take precedence over direct "carbonyl-sequestering" reactions, but how this reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 49 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…Burcham et al showed in mouse hepatocytes that exposure to allyl alcohol and its metabolite acrolein led to protein carbonylation, which correlated with hepatocyte death. They later showed that the acrolein scavenger hydralazine effectively trapped acrolein adducts in vivo to reduce allyl alcoholmediated hepatotoxicity in mice, and that mobilization of the chaperone protein HSP90 was protective against acroleininduced carbonylation (Burcham et al, 2012). Acrolein was suggested to play a role in liver injury in a murine model of early alcoholic liver disease and two novel in vivo protein targets for acrolein were identified: neutral alpha-glucosidase AB and nesprin-1 (Galligan et al, 2012).…”
Section: Protein Adductionmentioning
confidence: 99%
“…Burcham et al showed in mouse hepatocytes that exposure to allyl alcohol and its metabolite acrolein led to protein carbonylation, which correlated with hepatocyte death. They later showed that the acrolein scavenger hydralazine effectively trapped acrolein adducts in vivo to reduce allyl alcoholmediated hepatotoxicity in mice, and that mobilization of the chaperone protein HSP90 was protective against acroleininduced carbonylation (Burcham et al, 2012). Acrolein was suggested to play a role in liver injury in a murine model of early alcoholic liver disease and two novel in vivo protein targets for acrolein were identified: neutral alpha-glucosidase AB and nesprin-1 (Galligan et al, 2012).…”
Section: Protein Adductionmentioning
confidence: 99%
“…Treatment with aldehyde scavengers such as hydralazine is a possibility being explored (Kaminskas et al, 2004; Burcham et al, 2012). Major challenges in applying these approaches are developing drugs that cross the blood-brain barrier and relatively selectively affect the target cells.…”
Section: Therapeutic Implications Of Catecholamine Autotoxicitymentioning
confidence: 99%
“…Furthermore, recent studies have shown that several of the HSPs are adducted by 4‐hydroxynonenal, a reactive breakdown product of lipid peroxidation , and that siRNA knockdown of the transcription factor, HSF1, whose translocation to the nucleus is controlled by several of the HSPs markedly enhances the loss in cell viability associated with 4‐hydroxynonenal exposure . Likewise, brief treatment of A549 lung cells with heat altered the distribution of HSP 90 to intermediate filaments and this correlated well with protection from another Michael adducting carbonyl, acrolein . Finally, HSP 70i knockout mice are considerably more susceptible to the hepatotoxic effects of acetaminophen, a bioactivated liver toxicant .…”
Section: Resultsmentioning
confidence: 85%